Ieee Infocom 2004
DOI: 10.1109/infcom.2004.1354530
|View full text |Cite
|
Sign up to set email alerts
|

A key management scheme for wireless sensor networks using deployment knowledge

Abstract: Abstract-To achieve security in wireless sensor networks, it is important to be able to encrypt messages sent among sensor nodes. Keys for encryption purposes must be agreed upon by communicating nodes. Due to resource constraints, achieving such key agreement in wireless sensor networks is non-trivial. Many key agreement schemes used in general networks, such as Diffie-Hellman and public-key based schemes, are not suitable for wireless sensor networks. Pre-distribution of secret keys for all pairs of nodes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…In [10], the authors describe deployment knowledgebased random key pre-distribution scheme. This scheme is said to be efficient in reducing memory requirement of sensors in networks.…”
Section: Related Workmentioning
confidence: 99%
“…In [10], the authors describe deployment knowledgebased random key pre-distribution scheme. This scheme is said to be efficient in reducing memory requirement of sensors in networks.…”
Section: Related Workmentioning
confidence: 99%
“…The most commonly used solution is the probabilistic schemes (Xiao et al, 2007;Traynor et al, 2006;Al-Haija, 2010;Silva et al, 2008;Sohraby et al, 2007;Dong-Mei and Bing, 2006;Khalil and Ozdemir, 2012;Chan et al, 2003;Du et al, 2005;2004;Kuchipudi and Basha, 2012). Eschenauer and Gligor (2002) and Xiao et al (2007) were the forerunner to build the first algorithm based probability using the random graph theory that is called the basic scheme, this scheme contains 3 phases: Key pre-distribution phase (where key pool generates a large number of keys P, then each node randomly selects Science Publications JCS number of keys K which called key ring), shared key discovery phase (in this phase any two nodes can establish a secure link if they shared a common key in their key rings) and, key path establishment phase (each node tries to establish a path-key with any node in their transmission range but do not share a common key with it).…”
Section: Related Workmentioning
confidence: 99%
“…When the final node receives all the keys can create the new link key like the XOR of the received keys. Du et al (2004) proposed a novel random key predistribution scheme that exploits deployment knowledge and avoids unnecessary key assignments. They showed that the performance (including connectivity, memory usage and network resilience against node capture) of sensor networks can be substantially improved with the use of thier proposed scheme.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Random key predistribution scheme using Probability Density Function (PDF): The Du et al (2004) scheme uses deployment rectangles whose sizes strongly depend on the pdf of node deployment. This scheme exhibits better performance (connectivity and memory usage) and it keeps the sensor networks secure.…”
Section: Related Workmentioning
confidence: 99%